Neolithic Scotland : timber, stone, earth and fire - Noble, Gordon (Edinburgh University Press, 2006)
Offers an account of the Neolithic period in Scotland from its early traces around 4000 BC to the transformation of Neolithic society in the Early Bronze Age. This work interprets Scottish material in the context of debates and issues in European archaeology, and outlines the chronology of the Neolithic in Europe.